Sixteen properties of Eucalyptus Tereticornis wood for structural uses - Marta Cristina de Jesus Albuquerque Nogueira; Victor Almeida de Araujo; Juliano Souza Vasconcelos; André Luis Christoforo; Francisco Antonio Rocco Lahr (Bioscience Journal, 2020)
Forest Red Gum eucalypt provides a versatile wood and is converted into different purposes. However, such wood is somewhat limited in structural ends, which highlights the need to exploit this gap through diffusion of mechanical properties of such timber. Obtained results should assist engineers and architects in decision-making for its best building application. This paper studied two physical and fourteen mechanical properties evaluation of Eucalyptus tereticornis at two different moisture contents, following the prescriptions of Brazilian (ABNT NBR 7190: 1997) and North American (ASTM D-143-14: 2014) standard documents. Thus, 1091 repeats were carried out for all properties. By a moisture reduction from 30% to 12%, the bulk density and eleven strength properties statistically showed changes such as modulus of rupture (static bending, parallel and perpendicular compressions), modulus of elasticity (perpendicular compression and static bending), shear stress, tangential cleavage, and parallel and perpendicular hardnesses. Then, the Eucalyptus tereticornis timber could be better usable if is further applied for structural construction uses.